2009
DOI: 10.1002/uog.7502
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity is a potential source of error in mid‐trimester ultrasound estimation of gestational age

Abstract: ObjectivesTo investigate the possible impact of maternal obesity on ultrasonographic dating of pregnancy. (OR, 1.65; 95% CI, 1.45; 95% CI, Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 22 publications
6
17
0
3
Order By: Relevance
“…The impact of abdominal fat on image quality was discussed by Simic et al [20]. They concluded that the estimation of gestational age in obese women as being shorter according to ultrasound than according to last menstrual period might be due to erroneous sonographic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of abdominal fat on image quality was discussed by Simic et al [20]. They concluded that the estimation of gestational age in obese women as being shorter according to ultrasound than according to last menstrual period might be due to erroneous sonographic measurements.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Given the potential for such systematic sources of error, 28 we used an algorithm that leverages all available estimates of gestational age to identify records with likely errors in dating.…”
Section: Figurementioning
confidence: 99%
“…Studies have shown that last menstrual period and ultrasound may be unreliable, particularly in obese women, although evidence points to a lengthening of the delivery date which would underestimate rather than overestimate gestational age at delivery biasing towards the null with respect to the analyses presented here. 3637 The primary predictor, prepregnancy weight based on self-report on the birth certificate, has been validated. 3839 There is some concern that overweight and obese women may underestimate their prepregnancy weight which will lead to an overestimate of weight gain in this population.…”
Section: Commentmentioning
confidence: 99%